1999
DOI: 10.1073/pnas.96.14.8138
|View full text |Cite
|
Sign up to set email alerts
|

Tissue factor is required for uterine hemostasis and maintenance of the placental labyrinth during gestation

Abstract: We employed a novel mouse line that expresses low levels of human tissue factor (TF) in the absence of murine TF to analyze the role of TF in gestation. Low-TF female mice had a 14-18% incidence of fatal postpartum uterine hemorrhage, suggesting that TF plays an important role in uterine hemostasis. Low-TF female mice mated with low-TF male mice had a 42% incidence of fatal midgestational hemorrhage (n ‫؍‬ 41), whereas no fatal midgestational hemorrhages were observed in low-TF female mice mated with wild-type… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
96
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(103 citation statements)
references
References 37 publications
7
96
0
Order By: Relevance
“…[35][36][37] TF is best known as the primary cellular initiator of blood coagulation. 38 Although TF is required for uterine hemostasis and maintenance of the placental labyrinth during gestation, 39 increased placental TF expression can result in pregnancy complications such as preeclampsia (PE). 40,41 We previously demonstrated that pregnancy loss induced by antiphospholipid antibodies in mice is associated with increased TF expression.…”
Section: Discussionmentioning
confidence: 99%
“…[35][36][37] TF is best known as the primary cellular initiator of blood coagulation. 38 Although TF is required for uterine hemostasis and maintenance of the placental labyrinth during gestation, 39 increased placental TF expression can result in pregnancy complications such as preeclampsia (PE). 40,41 We previously demonstrated that pregnancy loss induced by antiphospholipid antibodies in mice is associated with increased TF expression.…”
Section: Discussionmentioning
confidence: 99%
“…Although the primary function of TF in the adult is to initiate blood coagulation (reviewed in Edgington et al, 1991), recent studies suggest that TF may contribute to blood vessel maturation in the developing embryo (Bugge et al, 1996;Carmeliet et al, 1996), to maintenance of the placental labyrinth during gestation (Erlich et al, 1999), and to tumor angiogenesis (Contrino et al, 1996). Tissue factor has also been implicated as a determinant of metastatic potential in melanoma cells (Mueller et al, 1992;Bromberg et al, 1995) and expression of TF in the stromal compartment of breast carcinomas has been shown to correlate with progression to invasive cancer (Contrino et al, 1996;Vrana et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…This may be critical as the placenta represents a hypercoagulable environment. Indeed, embryonic placental tissue factor procoagulant activity in the trophoblasts is essential for normal placental development (27). Furthermore, it seems that maternal fibrinogen and its conversion to fibrin is also required (in controlled quantities) for placental stabilization and the anchoring of placental trophoblasts to the maternal decidua (28).…”
Section: Discussionmentioning
confidence: 99%